Functional Versatility of the CDK Inhibitor p57Kip2 - Creff, Justine; Besson, Arnaud (Frontiers in Cell and Developmental Biology, 2020)
p57Kip2 is a cyclin/CDK inhibitor of the Cip/Kip family, with p21Cip1 and p27Kip1. Unlike the other family members, p57Kip2 has a unique role during embryogenesis and is the only CDK inhibitor required for embryonic development. p57Kip2 is encoded by the imprinted gene CDKN1C, which is the gene most frequently silenced or mutated in the genetic disorder Beckwith-Wiedemann Syndrome (BWS), characterized by multiple developmental anomalies. Although initially identified as a cell cycle inhibitor based on its homology to p21Cip1 and p27Kip1, multiple novel functions have been ascribed to p57Kip2 in recent years that participate in the control of various cellular processes, including apoptosis, migration and transcription. Here, we will review our current knowledge on p57Kip2 structure, regulation, and its diverse functions during development and homeostasis, as well as its potential implication in the development of various pathologies, including cancer.